A grounded theory approach to the investigation of cadastral activities and processes of Gweru municipality - Mudare, Benevolence (Midlands State University, 2019)
This paper explores the power of Constructivist grounded theory methodology to discover the theory of the Gweru Cadastral processes and activities. The researcher used the tools and techniques of constructivist grounded theory to mine rich data at Gweru council which he then performed data analysis to yield analytic categories. The researcher then used these analytic categories to write the Gweru cadastral processes theory which he then compared with the theory within the domain of land governance.